2008
DOI: 10.1152/ajpregu.00029.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation and inhibition of the micturition reflex by penile afferents in the cat

Abstract: Woock JP, Yoo PB, Grill WM. Activation and inhibition of the micturition reflex by penile afferents in the cat. Am J Physiol Regul Integr Comp Physiol 294: R1880-R1889, 2008. First published April 23, 2008 doi:10.1152/ajpregu.00029.2008.-Coordination of the urinary bladder and the external urethral sphincter is controlled by descending projections from the pons and is also subject to modulation by segmental afferents. We quantified the effects on the micturition reflex of sensory inputs from genital afferent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
92
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(118 citation statements)
references
References 66 publications
23
92
3
Order By: Relevance
“…Stimulation at 1T and 2T produced significant bladder inhibition, but was less robust, consistent with results of other studies (53). The nomenclature used here for threshold and stimulation amplitude (1T ϭ BCR reflex EMG threshold) should be distinguished from other studies, where 1T is determined as the threshold to evoke inhibition and would, in general, represent a higher amplitude.…”
Section: Effectiveness Of Stimulation-evoked Inhibitionsupporting
confidence: 85%
See 1 more Smart Citation
“…Stimulation at 1T and 2T produced significant bladder inhibition, but was less robust, consistent with results of other studies (53). The nomenclature used here for threshold and stimulation amplitude (1T ϭ BCR reflex EMG threshold) should be distinguished from other studies, where 1T is determined as the threshold to evoke inhibition and would, in general, represent a higher amplitude.…”
Section: Effectiveness Of Stimulation-evoked Inhibitionsupporting
confidence: 85%
“…Electrodes were composed of single platinum contacts embedded within silicone cuffs, and pulse generators (Pulsar 6bp, FHC) were used to deliver stimulation (0.1-ms cathodic stimulus pulses, for 20 -30 s) between the cuffs and subcutaneous 20-G needles. Both the PN and DNP were stimulated at 10 Hz, a frequency previously shown to produce strong bladder inhibition in cats (53). The stimulation amplitude was one (1T), two (2T), or three (3T) times the threshold (T) that produced a bulbocavernosus reflex (BCR) EMG response in the EAS with 1-Hz stimulation.…”
Section: Methodsmentioning
confidence: 99%
“…This finding is consistent with clinical neuromodulation studies showing that conditional and continuous DNP stimulation significantly increases bladder capacity (Kirkham et al 2001). The stimulus parameters to evoke the response are also consistent with animal studies showing that low-frequency DNP stimulation inhibits bladder contractions (Su et al 2012a;Woock et al 2008). Studies in adult cats also indicate that optimal inhibition of bladder contractions has a wider effective range of frequencies and amplitudes via DNP stimulation than other targets (pudendal, S 1 ) (Snellings and Grill 2012).…”
Section: Discussionsupporting
confidence: 77%
“…The study results demonstrate significant overlap in the neurostimulation parameters (amplitudes and frequencies) both for producing an increase in the interval of voiding during filling and for evoking or altering neuronal responses of MRF neurons in the rostral medulla, a site known to be involved in the control of sexual function (Marson and McKenna 1990). Previous studies examining neurostimulation for altering urinary physiology have demonstrated a U-shaped inhibitory curve with maximal effects at frequencies near 10 Hz (Snellings and Grill 2012;Su et al 2012aSu et al , 2012bWoock et al 2008). Interestingly, the present results with neurostimulation effects on MRF neuronal responses showed a plateau, or sigmoidal, effect with respect to frequency.…”
Section: Discussionmentioning
confidence: 71%
“…Further, abolition of stimulationevoked bladder contractions following administration of hexamethonium bromide confirmed that contractions were generated by pelvic efferent activation via the pelvic ganglion. These findings indicate that pudendal afferent stimulation evokes bladder contractions through convergence with pelvic afferents to increase pelvic efferent activity.cat; micturition; parasympathetic; sympathetic DEPENDING ON THE STIMULATION frequency, electrical stimulation of pudendal afferents evokes spinal reflexes that either inhibit the bladder and promote continence or excite the bladder and cause micturition in both cats (5,6,41,45,49) and persons with spinal cord injury (48). Previous results suggest that bladder inhibition by pudendal afferent stimulation arises from activation of hypogastric efferents and subsequent synaptic and ganglionic inhibition of parasympathetic efferents (8, 30), but the mechanisms of bladder excitation by pudendal afferent stimulation are not known.…”
mentioning
confidence: 99%